The Impact of Mass Media on Political Mobilization Process in Plateau State Radio Television Corporation, Jos (PRTVC), Nigeria - Bappayo, Abubakar; Abubakar, Ahmad; Kirfi, Yushau Haruna (NIU Journal of Humanities, 2021)
The aim of this study is to identify the impact of Mass Media in the Political mobilization process. The study was restricted to Jos city and its environs due to some unavoidable factors. Through personal contacts with the staff of Plateau State Radio Television Corporation Jos (PRTVC), questionnaire administration, documented materials, books, journals, newspapers, seminars and direct observation, the researcher was able to carry out this study. Also, the objective of the study was to determine the level interference of government in the activities of mass media affects the political mobilization process. The population consists of all the staff of Plateau Radio Television Corporation Jos (PRTVC) who answered the simple designed choice and opened questionnaires. The sample size of 196 employees of Plateau Radio Television Corporation Jos was used to gather relevant information for analysis. The researcher used frequency and percentage as a statistical tool of analysis to analyze all data collected. The study established that without a vibrant press and free flow of information, government cannot fully function to its full potentials. It also revealed that freedom of the press is vital to the growth of Nigerians democracy. The research thus recommends that in order to ensure, efficient and unbiased political mobilization by the mass media, there Should be total autonomy, which will in turn ensure a free and independent press. Keywords: Impact, Mass Media, Political, Mobilization, Radio and Television.